Preventive effect of sensorimotor exercise and resistance training on chemotherapy-induced peripheral neuropathy: a randomised-controlled trial - Müller, Jana; Weiler, Markus; Schneeweiss, Andreas; Haag, Georg Martin; Steindorf, Karen; Wick, Wolfgang; Wiskemann, Joachim (British journal of cancer, 2021)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common, unpleasant and usually long-lasting side effect of neurotoxic chemotherapeutic agents. This study aimed to investigate the preventive potential of sensorimotor- (SMT) and resistance training (RT) on CIPN.